Belgium-Luxembourg economic union - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1971)
The part 1 of the present survey attempts to throw light on the reasons behind Belgium's relatively good price performance during the period. The part 2 discusses trends, policies and prospects in the current year when significant inflationary pressures have been building up, partly in response to the shift in January to a tax on value added (TVA).
hza 14/02/2019
Loans
Keywords: Economic history; Belgium; Luxembourg